Finance literacy, digital literacy and Micro, Small, Medium Enterprise (MSME) performance - Iriani, Latifah Dian; Hidayah, Nurul; Andjar, Febry Jein (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
The low level of female participation in the labor market affects the income gap between men and women. However, the informal sector tends to be of interest to women, especially in the Micro, Small, and Medium Enterprises sector (MSMEs). MSMEs have a very vital role in Indonesia's economic growth. However, the development of MSMEs for women entrepreneurs has obstacles such as low access to business capital and marketing of MSME products. This is influenced by the low level of financial literacy and digital literacy for women in the MSME sector. This paper aims to ascertain the relationship among financial literacy and the performance of women MSMEs specifically with the variable of digital literacy as a moderator. This paper uses primary data through the distribution of questionnaires to women entrepreneurs (MSMEs) in Sorong Regency. The data analysis technique uses Structural Equation Model (SEM) and Partial Least Square (PLS). The results show that financial literacy has positive and significantly affect MSME performance. While, digital literacy has a positive effect on MSMEs performance. In addition, digital literacy has a positive effect in moderating the relationship between financial literacy and MSMEs performance for female entrepreneurs. However, financial literacy is not significantly effect on the performance of MSMEs for women.